Políticas públicas e crítica queer: algumas questões sobre identidade LGBT - Sampaio, Juliana Vieira (2014)
In the eighties, the LGBT movement in Brazil began a political partnership with the State in order to address the AIDS epidemic. The success of those actions resulted in new political agendas aiming to ensure better care for LGBT people. Recent policies were expanded but had to adapt to the current mode of political representation, an essencialist type of identity politics. This paper aims to discuss how the essencialism that grounds sexpolitics is negotiated in LGBT public policies and how a “strategic identity” can affect the ways of living of those who don’t fit heteronormative standards. From a critical discursive perspective, five documents of LGBT public policies were studied based on Foucauldian and Queer Theory conceptual frames. We conclude that queer multitude politics may signal more radical and strong forms of political action.